2002
DOI: 10.1002/jemt.10046
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of adrenomedullin revealed by animal models

Abstract: The newly identified adrenomedullin (AM) gene codes for a potent, highly conserved vasodilator that is expressed in many tissues. Many biological functions have been ascribed to AM based on its broad expression pattern and numerous in vitro studies, and it is currently viewed as a multifunctional peptide hormone. Recent advances in gene manipulation have permitted the development of experimental animal systems to help distinguish between gene causes and effects in the context of otherwise normal physiology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…In this study, we find that adrenomedullin peptide, secreted from the epicardium, is a potent regulator of cardiomyocyte proliferation during embryogenesis. Since the discovery of adrenomedullin (protein ¼ AM, gene ¼ Adm) in 1993 (Kitamura et al, 1993), many diverse biological functions have been described for this small circulating peptide during development, normal physiology and disease (Caron and Smithies, 2002;Karpinich et al, 2011). We, and others, have previously shown that genetic deletion of the highly conserved Adm gene in mice causes embryonic lethality at mid-gestation (Caron and Smithies, 2001;Shindo et al, 2001;Shimosawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we find that adrenomedullin peptide, secreted from the epicardium, is a potent regulator of cardiomyocyte proliferation during embryogenesis. Since the discovery of adrenomedullin (protein ¼ AM, gene ¼ Adm) in 1993 (Kitamura et al, 1993), many diverse biological functions have been described for this small circulating peptide during development, normal physiology and disease (Caron and Smithies, 2002;Karpinich et al, 2011). We, and others, have previously shown that genetic deletion of the highly conserved Adm gene in mice causes embryonic lethality at mid-gestation (Caron and Smithies, 2001;Shindo et al, 2001;Shimosawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among its many functions ADM has been shown to play a key role in mammalian development, as ADM knockout in mice is embryonically lethal (Garayoa et al, 2002; Ando and Fujita, 2003). Expression studies have, however, shown that ADM is initially limited to discrete embryonic regions, whereas at later stages of development it is nearly ubiquitously expressed (Montuenga et al, 1997, 1998; Caron and Smithies, 2002). While its exact mechanism(s) of action during development are not fully characterized, its expression coincides with the onset of both differentiation, for example during bone formation, and several chemotactic cell processes, including neural crest cell migration (Montuenga et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…growth. [5][6][7] Depending on the particular cell type, AM may promote or inhibit cell growth. 8,9 Although AM is expressed in normal prostate epithelium and prostate cancer, its function in the prostate remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…AM appears to be ubiquitously expressed 2,5 and can perform a variety of functions, including vasodilatation, bronchodilation, hormone secretion control, renal homeostasis and regulation of cell growth. [5][6][7] Some cell types are stimulated to proliferate by AM, 7,8 whereas other cell types are growth-inhibited. 9 The calcitonin receptor-like receptor (CRLR), in conjunction with receptor activity-modifying protein-2 (RAMP-2) and -3 (RAMP-3), functions as AM receptors in numerous cell types.…”
mentioning
confidence: 99%